Одна тень на двоих: [роман] / Татьяна Устинова - Устинова Татьяна Витальевна (Первая среди лучших, 2003)
Экземпляры: Ф. 1 (20191029) / Инвентарный номер: 38584 / Цена: 20.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: У 80 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44